The Filter of Attention and Indissoluble Attractors in Eighteenth-Century Mock-Heroic Poetry. - Koehler, Margaret (Modern Philology, 2010)
The article focuses on the aspects of the 18th century mock-heroic poetry which engages vitally with the phenomenon of attention. It mentions that cognitive psychologists have alternately conceived of attention as a filter that selects some stimuli over others and as a spotlight that enhances a distinct area. Critics have also noted the mock-heroic's cultivation of split awareness and its elevation of the trivial in ways that reach beyond satiric irony.